The creativity of contract lecturers in fostering student learning motivation in the industrial era 4.0 - Suryaningrat, Gamal; Askar, Askar; Syahid, Ahmad (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2023)
This paper discusses the creativity of adjunct lecturers in fostering student learning motivation in the digital era. The study employs a qualitative method. Qualitative research describes and explains the empirical research findings obtained in the field. Data is collected through field observations, in-depth interviews, and document analysis. The research findings indicate that the ability of adjunct lecturers to foster student learning motivation in the digital era necessitates good lesson planning. Lecturers can design strategies and teaching methods according to the needs and characteristics of the students. These young lecturers also need to combine learning with entertainment to motivate students. Furthermore, the creativity of adjunct lecturers in fostering student motivation in the digital era includes being communicative instructors. These adjunct lecturers also utilize the advancements in social media as a learning resource, create educational videos, and integrate current issues with course materials. This research implies that lecturers are expected to pay more attention to creativity in implementing the learning process. Adequate learning facilities support this creativity.